Thermodynamics, Environmental and Sustainability Impacts of a Turbofan Engine Under Different Design Conditions Considering Variable Needs in the Aviation Industry - Aygun, Hakan; Sheikhi, Mohammad Rauf; Caliskan, Hakan (Wiley-V C H Verlag Gmbh, 2024)
In this study, thermodynamic analysis is implemented to the kerosene-fuelled high by-pass turbofan (HBP-TF) engine to assess entropy, exergy, environmental, and sustainability metrics for different design variables such as pressure ratio of high-pressure compressor (HPC-PR) ranging from 7.5 to 8.5 and turbine inlet temperature (TIT) varying from 1400 to 1525 K considering variable needs in the aviation industry. As a novelty, entropic improvement potential (EIP) index for turbomachinery components and specific irreversibility production for the whole engine are calculated. Sustainability-based parameters for different cases are compared with the baseline values of the HBP-TF engine. The combustor has the highest entropy production of 44.4425 kW K-1 at the baseline. The higher TIT increases the entropy production of the combustor by 16.56%, whereas the higher HPC-PR decreases it by 5.83%. The higher TIT and HPC-PR favorably affect the sustainable efficiency factor of the engine, which is observed as 1.5482 at baseline and increases by 4.5% and 0.058% with the increment of TIT and HPC-PR, respectively. The higher TIT and higher HPC-PR results in lowering sustainability of the engine. The specific irreversibility production of the engine decreases by 3.78% and 0.1171% respectively, as TIT and HPC-PR reach the highest point considered in the study. Thermodynamic analysis is applied to the kerosene fuelled high by-pass turbofan (HBP-TF) engine to assess entropy, exergy, environmental and sustainability metrics for different design variables. As a novelty, entropic improvement potential index for turbomachinery components and specific irreversibility production for the whole engine are computed. Sustainability-based parameters for different cases are compared with the baseline values of HBP-TF engine.image
Keywords: entropy; environmental effect; exergy; sustainability; turbofan